Pemberdayaan Masyarakat Melalui Pelatihan Tata Rias dalam Mengurangi Pengangguran Usia Produktif di Kabupaten Enrekang - Alvitriyanti, Devi; ., Suparman; ., Haerusman; ., Saidang; Hatta, M. (Universitas Muhammadiyah Makassar, 2025)
Productive age unemployment is a social problem that has a direct impact on community welfare and regional economic growth. In Enrekang Regency, the increase in unemployment rates from year to year shows that the efforts to overcome it have not been optimal, especially for people who are not absorbed in the formal workforce. This study aims to examine the effectiveness of make-up training as a community empowerment strategy in reducing productive age unemployment. This study is also expected to provide alternative solutions based on non-formal education that are in accordance with local potential. The method used is descriptive qualitative with data collection techniques through in-depth interviews, participatory observation, and documentation. The results of the study showed that make-up training had a positive impact on improving participants' skills, building motivation for entrepreneurship, and giving rise to the initiative to open make-up services independently. Participants showed high enthusiasm in the learning process and some began to practice their skills in the community. This training has been proven to not only improve technical skills, but also shape entrepreneurial mindsets and economic independence. Therefore, skills training based on local potential such as make-up can be an effective and sustainable alternative solution in overcoming productive age unemployment in the region.